2006
DOI: 10.1055/s-2006-948308
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum 25-Hydroxyvitamin D Concentrations are Associated with Insulin Resistance and Obesity in Women with Polycystic Ovary Syndrome

Abstract: Insulin resistance (IR) and central obesity are common features of the polycystic ovary syndrome (PCOS). Vitamin D is thought to play a role in the pathogenesis of type 2 diabetes by affecting insulin metabolism. The aim of our study was to investigate the effect of 25-hydroxyvitamin D (25-OH-VD) on metabolic parameters and IR in PCOS. In 120 untreated PCOS patients (median age 28 years) levels of 25-OH-VD (radioimmunoassay method provided by DiaSorin), calcium and anorganic phosphate were measured. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
202
4
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(260 citation statements)
references
References 38 publications
25
202
4
19
Order By: Relevance
“…These results conflict with previous studies' findings that hypovitaminosis D is associated with PCOS (1). Furthermore, other authors have suggested that vitamin D deficiency is associated with PCOS only among obese women (30,31). Moreover, another study found that hypovitaminosis D was associated with insulin resistance, regardless of the patient's body mass index (32).…”
Section: Resultsmentioning
confidence: 99%
“…These results conflict with previous studies' findings that hypovitaminosis D is associated with PCOS (1). Furthermore, other authors have suggested that vitamin D deficiency is associated with PCOS only among obese women (30,31). Moreover, another study found that hypovitaminosis D was associated with insulin resistance, regardless of the patient's body mass index (32).…”
Section: Resultsmentioning
confidence: 99%
“…The biological mechanisms by which vitamin D may influence the MetS have not been completely elucidated. Several studies reported that 25(OH)D 3 was inversely related to percentage body fat (37,38), elevated BP (39-41), elevated glucose or IR (11,(42)(43)(44), and triglycerides (45) and positively associated with HDL-cholesterol (42). In particular, using data from the Third National Health Examination and Nutrition Survey (NHANES) (46).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies had an observational design (18,19,20,21,22,23,24,25,26,27,28,29), employing a crosssectional or case-control design, with vitamin D status as one of the preliminary outcomes. A summary of these studies is given in Table 1.…”
Section: The Association Between Vitamin D Status and Metabolic Distumentioning
confidence: 99%
“…The studies included premenopausal women (14-50 years) of various ethnicities, with the number of participants ranging from 45 to 400. Different stratifications were used: seven studies compared PCOS women with controls (19,20,22,23,24,27,28), three studies compared lean vs obese PCOS women (18,21,26), one study compared PCOS women with and without the metabolic syndrome (25), and one study solely included PCOS women (29). Large differences were found in the prevalence of vitamin D deficiency (defined as serum 25OHD levels !50 nmol/l), varying from 37% in a study carried out in Italy (21) to 72% in a study carried out in Scotland (19).…”
Section: The Association Between Vitamin D Status and Metabolic Distumentioning
confidence: 99%